Gait Variability, Not Walking Speed, Is Related to Cognition in Adolescents With Multiple Sclerosis. (January 2019) - Kalron, Alon; Achiron, Anat; Menascu, Shay
Gait variability is associated with cognitive performance in people with central neurologic damage illnesses, which includes multiple sclerosis. However, presently, there have been no data available as to whether this association exists in adolescents with multiple sclerosis. Therefore, our objective was to investigate the association between gait variability and cognition in adolescents with multiple sclerosis encompassing 48 recently diagnosed adolescents with multiple sclerosis (26 girls; 22 boys), average age of 16.0 years (SD = 2.2), and an Expanded Disability Status Scale (EDSS) score of 1.6 (SD = 1.3). Walking speed and gait variability expressed by the coefficient of variation of the mean step time was studied using an electronic walkway. A computerized cognitive battery of tests evaluated cognition. Cognitive outcome measurements included verbal and nonverbal memory, executive function, visual spatial processing, verbal function, attention, information processing speed, and motor skills. Mean walking speed was 76.9 cm/s (SD = 57.6); mean step time variability was 3.5 (SD = 1.3) and the global cognitive score was 93.9 (SD = 12.5). According to linear regression analysis, a significant association was found between step time variability, cognitive subdomains of attention, and information processing speed. After incorporating walking speed into the model, the association remained significant. Increased gait variability, not walking speed, is suggested as a clinical marker of cognitive performance in minimally disabled adolescents with multiple sclerosis.